Metatranscriptomic insights into aerobic biotransformation of 6:2 fluorotelomer sulfonate by an enrichment culture under sulfur-limiting conditions - Kabir, Md G.; Tang, Zhiwen; Zhang, Xiqian; Coulon, Frederic; Tiehm, Andreas; Song, Xin (American Chemical Society (ACS), 2025)
6:2 Fluorotelomer sulfonate (6:2 FTS), an alternative for PFOS, has become an environmental concern due to its toxicity. This study investigated the aerobic biotransformation of 6:2 FTS under sulfur-limiting conditions using an enrichment culture, SXC01. The enriched culture achieved ≥99.5% degradation of 6:2 FTS at initial concentrations of 0.5, 2.5, and 5 mg/L within 14 days, with notable corresponding defluorination ratios of 77.2%, 28%, and 16.8%, respectively. Eleven transformation products were identified and quantified over time, and the accumulation of intermediate product 6:2 FTUCA suggested that its further degradation may represent a rate-limiting step. Furthermore, the production of PFHxA is more significant than that of PFBA, suggesting the transformation of 6:2 FTUCA via 5:2 sFTOH pathway is more dominant than the other proposed alternative pathway. Metatranscriptomic analysis revealed the upregulation of key genes associated with desulfonation (e.g., ssuEADCB cluster, cysI, sbp, iscS) and defluorination (e.g., ladA, dehH, crcB, dhaA), indicating a synergistic metabolic network driving 6:2 FTS biotransformation. Active genera identified included Brucella, Rhodococcus, and Pseudoclavibacter. Moreover, the predominant Brucella anthropi SX009 was successfully isolated and shown to completely degrade 6:2 FTS within 14 days. This study provides novel insights into the mechanisms of 6:2 FTS biotransformation.
Keywords: Environmental Sciences; PFAS; 6:2 FTS; Biodegradation; Biotransformation pathway; Defluorination; Upregulated gene; Metatranscriptomic analysis